Letztbegründungen und Gott - Runggaldier, Edmund; Schick, Benedikt (De Gruyter, 2011)
This volume collects work from contemporary philosophers and theologians regarding justifications for the existence of God. Both classical and new proofs of God's existence are presented and critically discussed. The contributions also deal with questions regarding what sense such justifications have and what sort of meaning can come from arguing for the rationality of religious belief.